Identification of pyroptosis-related subtypes and establishment of prognostic model and immune characteristics in asthma - Yang, Fan; Wang, Tieshan; Yan, Peizheng; Li, Wanyang; Kong, Jingwei; Zong, Yuhan; Chao, Xiang; Li, Weijie; Zhao, Xiaoshan; Wang, Ji (Frontiers in Immunology, 2022)
Abstract: Background: Although studies have shown that cell pyroptosis is involved in the progression of asthma, a systematic analysis of the clinical significance of pyroptosis-related genes (PRGs) cooperating with immune cells in asthma patients is still lacking. Methods: Transcriptome sequencing datasets from patients with different disease courses were used to screen pyroptosis-related differentially expressed genes and perform biological function analysis. Clustering based on K-means unsupervised clustering method is performed to identify pyroptosis-related subtypes in asthma and explore biological functional characteristics of poorly controlled subtypes. Diagnostic markers between subtypes were screened and validated using an asthma mouse model. The infiltration of immune cells in airway epithelium was evaluated based on CIBERSORT, and the correlation between diagnostic markers and immune cells was analyzed. Finally, a risk prediction model was established and experimentally verified using differentially expressed genes between pyroptosis subtypes in combination with asthma control. The ssGSEA method was applied to analyze differences in immune cell infiltration between high- and low-risk groups, and cMAP database and molecular docking were utilized to predict potential therapeutic drugs. Results: Nineteen differentially expressed PRGs and two subtypes were identified between patients with mild-to-moderate and severe asthma conditions. Significant differences were observed in asthma control and FEV1 reversibility between the two subtypes. Poor control subtypes were closely related to glucocorticoid resistance and airway remodeling. BNIP3 was identified as a diagnostic marker and associated with immune cell infiltration such as, M2 macrophages. Combined with the control of asthma, a risk prediction model that includes four genes was constructed to distinguish between high- and low-risk groups with significant differences in immune cells between groups effectively. Small molecules obtained from the cMAP database that may have therapeutic effects on asthma are mainly DPP4 inhibitors. Conclusion: Pyroptosis and its mediated immune phenotype are crucial in the occurrence, development, and prognosis of asthma. The predictive models and drugs developed on the basis of PRGs may provide new solutions for the management of asthma.